Global Supply Shocks, Inflation Dynamics, and Firm Adaptation Strategies - Aulia, Zahrani; Qurrota A'yun, Annisa (Inovasi Analisis Data, 2025)
Purpose: This paper investigates how manufacturing companies deploy adaptation strategies during periods of global supply chain disruption, while putting a premium on the role of managerial capabilities in strengthening organizational resilience.Method: Utilised an explanatory quantitative approach by employing structural equation modeling to analyze a dataset of survey responses from manufacturing firms experiencing ComPlex global supply scenarios.Findings: The study shows that effective adaptation results from the combined contributions of risk management capabilities to cope with external disruption and to manage internal risks. The work contends that organisations which successfully capitalise on managerial capabilities develop higher capacity to convert supply chain challenges into strategic opportunities through improved resistance and competitive positioning.Novelty: This study is one of the first to propose an integrative approach that connects the management of external shock with internal capability development, and enriches our understanding about how organizations adapt in emerging economy contexts.Implications: The results offer practical guidelines to managers for developing adaptive organizations, and make notable theoretical contributions to the literature of supply chain resilience by redefining adaptation as an evolutional capability-build process.